WOMEN CASUAL CLOTHES WITH TEACHING BATIK MOTIF PRINCE OF SAMUDRA AT MOUNT KEMUKUS - Wati, Bintang Kusuma; Andini, Bertha Galuh (Runtas : Journal Of Arts And Culture, 2023)
Prince Samudra teachings on Mount Kemukus covering agriculture, culture, martial arts and Islamic religious knowledge are works of art that are applied to adult women's casual clothing, with this final project the author wants to bring and introduce to the general public through fashion trends. The process of creating a work starts from the exploration stage (searching for sources of ideas, concepts, and the basis for creation), design (the design of the work), and embodiment (making the work). The process of making works of art goes through the initial stages of making designs, making patterns, preparing tools and materials, scraping, printing, dyeing colors. sewing and finishing. The technique used in this work is hand-drawn batik using night wax as the main tool, canting, primisima cloth " Golden chariot" and naptol dye. The results in the creation of this work are 5 adult women's casual clothing which are titled according to the symbolic philosophy and meaning implied in each motif, namely work 1 with the title Pulun, work 2 with the title Anacara, work 3 with the title Adisaktiman, work 4 with the title Smara Religion, and 5 works entitled Kaharep. Each of the works created reflects the storyline of Prince Samudra's teaching on Mount Kemukus with the appearance of characters spreading agricultural science, cultural science, martial arts and religious knowledge.